2019
DOI: 10.1021/acsomega.9b02976
|View full text |Cite
|
Sign up to set email alerts
|

Mg–Phenolic Network Strategy for Enhancing Corrosion Resistance and Osteocompatibility of Degradable Magnesium Alloys

Abstract: Magnesium-based alloys are the most widely used materials for degradable metallic implants and have considerable potential for bone applications owing to their excellent stimulating effect on osteogenesis. However, their high corrosion rate limits their structural stability and causes oxygen deficiency and an excessive increase in the pH around the defect area during bone healing. Magnesium oxides, which are the main corrosion products of Mg, are nontoxic materials with useful effects on new bone formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
0
14
0
1
Order By: Relevance
“…Various metal ions, such as Cu 2+ , Mg 2+ , Sr 2+ , gallium ions (Ga 3+ ), and Co 2+ , have been found to improve the microenvironment of bone defects and promote bone repair. [18][19][20][21][22] The mechanisms of promoting the osteogenesis of these metal ions are numerous and complex. 23 We will discuss the functionality of metal ions in the treatment of bone defects from the aspects of directly promoting bone tissue regeneration, inhibiting osteoclasts, promoting angiogenesis, and improving the microenvironment through a local antibacterial effect (Table 1).…”
Section: Function Of Metal Ions In the Treatment Of Bone Defectsmentioning
confidence: 99%
“…Various metal ions, such as Cu 2+ , Mg 2+ , Sr 2+ , gallium ions (Ga 3+ ), and Co 2+ , have been found to improve the microenvironment of bone defects and promote bone repair. [18][19][20][21][22] The mechanisms of promoting the osteogenesis of these metal ions are numerous and complex. 23 We will discuss the functionality of metal ions in the treatment of bone defects from the aspects of directly promoting bone tissue regeneration, inhibiting osteoclasts, promoting angiogenesis, and improving the microenvironment through a local antibacterial effect (Table 1).…”
Section: Function Of Metal Ions In the Treatment Of Bone Defectsmentioning
confidence: 99%
“…The content of Zn in the surface of Zn-contained PDA films ranged from 1.81 to 2.58 at%. It was widely reported that metal ions can be chelated with phenolic groups [ 39 , 40 ], whereas a dopamine molecule contains two phenolic hydroxyl groups. Therefore, the Zn ions can easy be chelated in PDA film.…”
Section: Resultsmentioning
confidence: 99%
“…Asgari et al prepared a magnesium oxide film coating on a Mg-based substrate and established a rat calvarial defect model. Their results revealed the improved osteo-compatibility and biodegradability of magnesium alloys ( Asgari et al, 2019 ). Zinc-based alloys can improve the low strength and brittleness of pure zinc and provide a novel biodegradable material for orthopedic applications.…”
Section: Current Progress and Future Directionsmentioning
confidence: 99%